2010
DOI: 10.1371/journal.pbio.1000384
|View full text |Cite
|
Sign up to set email alerts
|

A Large Fraction of Extragenic RNA Pol II Transcription Sites Overlap Enhancers

Abstract: A substantial fraction of extragenic Pol II transcription sites coincides with transcriptional enhancers, which may be relevant for functional annotation of mammalian genomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

51
827
6
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 804 publications
(886 citation statements)
references
References 79 publications
(152 reference statements)
51
827
6
2
Order By: Relevance
“…7B). Such overlapping lncRNAs might resemble enhancer-associated lncRNAs (De Santa et al 2010;Kim et al 2010;Ørom et al 2010;). …”
Section: Nearest Neighbor Analysis Of Lncrna Genesmentioning
confidence: 99%
“…7B). Such overlapping lncRNAs might resemble enhancer-associated lncRNAs (De Santa et al 2010;Kim et al 2010;Ørom et al 2010;). …”
Section: Nearest Neighbor Analysis Of Lncrna Genesmentioning
confidence: 99%
“…One unanticipated observation that emerged from multiple global studies of RNA polymerase II (Pol II) occupancy was that Pol II binds to a large number of intergenic AR-bound enhancers marked by histone H3 lysine 4 monomethylation (H3K4me1) and lysine 27 acetylation (H3K27ac) and produces enhancer-derived long noncoding RNAs (eRNAs) (8)(9)(10)(11). Although eRNAs are bidirectional and nonpolyadenylated, their induction correlates with the induction of adjacent exon-coding genes (9).…”
Section: Klk3e/ar/med1 Complex | Chromosomal Loopingmentioning
confidence: 99%
“…More globally, a recent comprehensive screen identified dozens of lincRNAs required to maintain pluripotency and suggested that these lincRNAs work in trans . Another class of ''enhancer RNAs'' may either be by-products of transcription (De Santa et al 2010;Kim et al 2010) or serve to activate gene expression in cis (Orom et al 2010;Wang et al 2011). Despite these intriguing studies of individual lincRNAs, generalizing these findings to thousands of lincRNAs remains a substantial challenge.…”
mentioning
confidence: 99%